Coevolution in the timing of GABAergic and pyramidal neuron maturation in primates. Issue 1861 (30th August 2017) - Charvet, Christine J.; Šimić, Goran; Kostović, Ivica; Knezović, Vinka; Vukšić, Mario; Babić Leko, Mirjana; Takahashi, Emi; Sherwood, Chet C.; Wolfe, Marnin D.; Finlay, Barbara L.
Abstract : The cortex of primates is relatively expanded compared with many other mammals, yet little is known about what developmental processes account for the expansion of cortical subtype numbers in primates, including humans. We asked whether GABAergic and pyramidal neuron production occurs for longer than expected in primates than in mice in a sample of 86 developing primate and rodent brains. We use high-resolution structural, diffusion MR scans and histological material to compare the timing of the ganglionic eminences (GE) and cortical proliferative pool (CPP) maturation between humans, macaques, rats, and mice. We also compare the timing of post-neurogenetic maturation of GABAergic and pyramidal neurons in primates (i.e. humans, macaques) relative to rats and mice to identify whether delays in neurogenesis are concomitant with delayed post-neurogenetic maturation. We found that the growth of the GE and CPP are both selectively delayed compared with other events in primates. By contrast, the timing of post-neurogenetic GABAergic and pyramidal events (e.g. synaptogenesis) are predictable from the timing of other events in primates and in studied rodents. The extended duration of GABAergic and pyramidal neuron production is associated with the amplification of GABAerigc and pyramidal neuron numbers in the human and non-human primate cortex.